Presentations of rings with a chain of semidualizing modules - Amanzadeh, Ensiyeh; Dibaei, Mohammad T. (MATHEMATICA SCANDINAVICA, 2017)
Inspired by Jorgensen et al., it is proved that if a Cohen-Macaulay local ring $R$ with dualizing module admits a suitable chain of semidualizing $R$-modules of length $n$, then $R\cong Q/(I_1+… +I_n)$ for some Gorenstein ring $Q$ and ideals $I_1,… , I_n$ of $Q$; and, for each $Λ \subseteq [n]$, the ring $Q/(\sum _{\ell \in Λ } I_\ell )$ has some interesting cohomological properties. This extends the result of Jorgensen et al., and also of Foxby and Reiten.